2017
DOI: 10.1021/acs.jpclett.6b02811
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Evidences of Mesoscopic-Scale Complexity in Neat Ionic Liquids and Their Mixtures

Abstract: Ionic liquids (ILs) represent a blooming class of continuously developing advanced materials, with the aiming of a green chemical industry. Their appealing physical and chemical properties are largely influenced by their micro- and mesoscopic structure that is known to possess a high degree of hierarchical organization. High-impact application fields are largely affected by the complex morphology of neat ionic liquids and their mixtures. This Perspective highlights new arising research directions that point to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 47 publications
8
100
0
Order By: Relevance
“…39,40 Small-angle neutron scattering (SANS) techniques have been utilised to further investigate IL structure. 27,41,42 These tend to agree with the notion that the PNPP is due to nanostructuring in the liquid. However, some contributions put forward an argument that the PNPP does not arise from nanoscale ordering, but is simply derived from a second-shell radial distribution.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…39,40 Small-angle neutron scattering (SANS) techniques have been utilised to further investigate IL structure. 27,41,42 These tend to agree with the notion that the PNPP is due to nanostructuring in the liquid. However, some contributions put forward an argument that the PNPP does not arise from nanoscale ordering, but is simply derived from a second-shell radial distribution.…”
Section: Introductionsupporting
confidence: 82%
“…27 The structures of IL mixtures are significantly less well understood than pure ILs. 1,40,42 Small angle X-ray scattering (SAXS) has been used to study binary IL mixtures of [ 44 These data suggest that IL structure in some binary IL mixtures may depend strongly on composition.…”
Section: Introductionmentioning
confidence: 99%
“…[11,[17][18][19][20][21][22][23][24][25][26] Recent studies suggest that the existence and dynamics of the aggregates in neat ionic liquids, associated with fluctuations of the polar and non-polar regions, correlate strongly with many of the physicochemical properties of ionic liquids including transport properties such as zero-shear viscosity, dc ionic conductivity, and static dielectric permittivity. [27][28][29][30][31][32] However, no efforts to exploit the mesoscale organization to design novel ionic liquids with unique physical and chemical properties have been reported. In this work, it is demonstrated that by mixing ionic liquids with varying degrees of solvophobic aggregation, it is feasible to design distinct liquids with macroscopic properties that significantly deviate from weighted contributions of the neat components.The local organization, or morphology, of the mesoscale aggregates is in part determined by the relative volume fractions of the polar and non-polar groups of the component ions.[11] In amphiphilic imidazolium, pyrrolidinium, piperidinium, quaternary phos-…”
mentioning
confidence: 99%
“…[11] An alternative approach to altering the polar and non-polar volume fractions is to consider mixtures of two or more ionic liquids with differing chemical structures. [29] We hypothesize, for instance, that in an amphiphilic ionic liquid mixed with a predominantly polar ionic liquid, which preferentially locates within the polar domain, the polar versus non-polar volume fraction and accordingly the morphology can be tuned by simply altering the composition. Any number of ion chemical structure combinations can be envisioned for the mixture components.…”
mentioning
confidence: 99%
“…As a matter of fact, their structure that was originally considered to be characterised by an onion-like alternation of opposite sign ions (similarly to the organisation in conventional high temperature molten salt, e.g., NaCl) has been discovered to show an enhanced level of organization, stemming from the alternation not only of charged and uncharged moieties, but also of polar and apolar domains. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] These alternations are now known to be fingerprinted by well-defined X-ray and/or neutron scattering 13,[21][22][23][24] features in the low momentum transfer (Q) range. The interest toward this feature is witnessed by the wealth of studies addressing its nature and dependence upon chemical nature of the ions, [25][26][27][28][29][30] temperature, 13,15,31 mixture composition, [32][33][34][35][36][37][38][39][40][41] and, only recently, pressure.…”
mentioning
confidence: 99%